1997
DOI: 10.1017/s0016672397002723
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for clonal structure of natural populations of free-living amoebae of the genus Naegleria

Abstract: Genetic diversity of natural populations of the two species Naegleria gruberi and N. australiensis collected at the same time in the same area was studied using multilocus enzyme electrophoresis (MLEE analysis). Reference strains and related species were also analysed for comparison. Five loci were found to be polymorphic and allowed identification of 19 different multilocus genotypes among 67 isolates -eight for N. gruberi and 11 for N. australiensis -none being common to the two species. Large departures fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
2
5
0
1
Order By: Relevance
“…Isoenzyme analysis also revealed that NG260 was separated from the other main Naegleria lineages (Robinson et al 1992). Thus, it is clear that N. gruberi is very heterogeneous as already demonstrated by biochemical and molecular analyses (Clark, Cross, and De Jonckheere 1989; Pernin and Cariou 1997; Robinson et al 1992). In the N. gruberi sample, the results obtained fit well with those of Robinson et al (1992), based on isoenzyme data: strains audl, NG273, and NG206 were phylogenetically closely related.…”
Section: Discussionsupporting
confidence: 55%
“…Isoenzyme analysis also revealed that NG260 was separated from the other main Naegleria lineages (Robinson et al 1992). Thus, it is clear that N. gruberi is very heterogeneous as already demonstrated by biochemical and molecular analyses (Clark, Cross, and De Jonckheere 1989; Pernin and Cariou 1997; Robinson et al 1992). In the N. gruberi sample, the results obtained fit well with those of Robinson et al (1992), based on isoenzyme data: strains audl, NG273, and NG206 were phylogenetically closely related.…”
Section: Discussionsupporting
confidence: 55%
“…The wide geographic distribution of some variants could suggest that clonal dispersion occurs. This mode of propagation has been observed for several protozoan organisms (23), including other Naegleria species (22). The similarities between the New Zealand and Australia strains and the Chooz and Cattenom strains (classified as South Pacific and South Pacificlike, respectively) could suggest that they all were derived from a unique ancestral group.…”
Section: Fig 1 (A Through E)supporting
confidence: 61%
“…Estudios realizados en la ameba dulceacuícola, Naegleria revelaron vía electroforesis, valores significativos de desequilibrio gamético, los cuales permitieron concluir relevantes aspectos sobre su modo de reproducción (Pernin & Cariou 1997). Los resultados revelaron desequilibrio en las tres poblaciones de Diplodon, es posible que este grupo presente un modo de reproducción alternativo, hermafroditismo facultativo y autofecundación.…”
Section: Resultsunclassified